2023
DOI: 10.1302/0301-620x.105b1.bjj-2022-0908.r1
|View full text |Cite
|
Sign up to set email alerts
|

Structurally intact and functionally incompetent foveal triangular fibrocartilage complex injuries

Abstract: Injury to the triangular fibrocartilage complex (TFCC) may result in ulnar wrist pain with or without instability. One component of the TFCC, the radioulnar ligaments, serve as the primary soft-tissue stabilizer of the distal radioulnar joint (DRUJ). Tears or avulsions of its proximal, foveal attachment are thought to be associated with instability of the DRUJ, most noticed during loaded pronosupination. In the absence of detectable instability, injury of the foveal insertion of the radioulnar ligaments may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Atzei and Luchetti (2011) further described the myriad of TFCC injuries and classified isolated foveal tears as a Class 3 injury, detectable by DRUJ arthroscopy. Crowe and Kakar (2023) further classified these injuries into partial and complete foveal tears, with and without DRUJ instability. All patients in this study demonstrated an arthroscopically confirmed foveal tear, and yet only five patients had DRUJ instability and 19 of the 24 patients had stable DRUJs upon clinical examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atzei and Luchetti (2011) further described the myriad of TFCC injuries and classified isolated foveal tears as a Class 3 injury, detectable by DRUJ arthroscopy. Crowe and Kakar (2023) further classified these injuries into partial and complete foveal tears, with and without DRUJ instability. All patients in this study demonstrated an arthroscopically confirmed foveal tear, and yet only five patients had DRUJ instability and 19 of the 24 patients had stable DRUJs upon clinical examination.…”
Section: Discussionmentioning
confidence: 99%
“…Unless present with a combined central tear (Minhas et al., 2022), the foveal insertion of the TFCC can only be visualized via DRUJ arthroscopy. Given that, we advocate for the routine use of DRUJ arthroscopy, especially if there are concomitant pathologies, such as central tear or ulnotriquetral ligament injury, to assess for the location and completeness of the foveal insertion of the TFCC (Crowe and Kakar, 2023).…”
Section: Discussionmentioning
confidence: 99%